O movimento estudantil de ocupação na Universidade Federal do Pampa – Unipampa campus Santana do Livramento: solução de conflitos e conquistas efetivas - (:unkn) unknown (Universidade Federal do Pampa, 2017)
This research had by objetc identify the conflict resolutions process at Universidade Federal do Pampa – UNIPAMPA Campus Santana do Livramento in front of the Student movement of occupation. To develop this study was used the method of field study by which it was analyzed the institution mentioned, targeting research the students, administrative technicians. The study has descriptive nature, qualitative bias and semi structured interview for data collection, as well as content analysis, in order to analyze the results obtained. The results of the research demonstrate that social movements are crucial to obtain rights deprived by the State, but they are also important to evidence the perspective that the state has taken in relation to its attitudes, thus, broadly speaking it was possible to perceive that besides solving conflicts the movements are able to establish standards that redirect the conduct of the State. It is crucial that the movement does not dissolve and always remain strong, cecause centralized movements in only a few places will not result in great achievements.
The student movement of occupation in the Universidade Federal do Pampa – campus Santana do Livramento: solution of conflicts and effective conquests
Keywords: Movimento social; Movimento estudantil; Ensino superior; Social movement; Student movement; Higher education; CNPQ::CIENCIAS SOCIAIS APLICADAS